Continuous diffraction of molecules and disordered molecular crystals. Issue 4 (7th July 2017) - Chapman, Henry N.; Yefanov, Oleksandr M.; Ayyer, Kartik; White, Thomas A.; Barty, Anton; Morgan, Andrew; Mariani, Valerio; Oberthuer, Dominik; Pande, Kanupriya
Abstract : The statistics of continuous diffraction patterns are determined and used to improve analysis of the diffraction of imperfect crystals of photosystem II. Abstract : The intensities of far‐field diffraction patterns of orientationally aligned molecules obey Wilson statistics, whether those molecules are in isolation (giving rise to a continuous diffraction pattern) or arranged in a crystal (giving rise to Bragg peaks). Ensembles of molecules in several orientations, but uncorrelated in position, give rise to the incoherent sum of the diffraction from those objects, modifying the statistics in a similar way as crystal twinning modifies the distribution of Bragg intensities. This situation arises in the continuous diffraction of laser‐aligned molecules or translationally disordered molecular crystals. This paper develops the analysis of the intensity statistics of such continuous diffraction to obtain parameters such as scaling, beam coherence and the number of contributing independent object orientations. When measured, continuous molecular diffraction is generally weak and accompanied by a background that far exceeds the strength of the signal. Instead of just relying upon the smallest measured intensities or their mean value to guide the subtraction of the background, it is shown how all measured values can be utilized to estimate the background, noise and signal, by employing a modified `noisy Wilson' distribution that explicitly includes the background. Parameters relating to the background and signal quantities can be estimated from the moments of the measured intensities. The analysis method is demonstrated on previously published continuous diffraction data measured from crystals of photosystem II [Ayyer et al. (2016), Nature, 530, 202–206].